Original articleThe association between cerebral amyloid angiopathy and atherosclerosis in patients with intracerebral hemorrhages - Mendel, Tadeusz Andrzej; Wierzba-Bobrowicz, Teresa; Stępień, Tomasz; Szpak, Grażyna Maria (Folia Neuropathologica, 2013)
Aim of the study : To analyze the incidence and grade of cerebral amyloid angiopathy (CAA) and atherosclerosis (AS) in cerebral vessels in patients who died from spontaneous intracerebral hemorrhage. Material and methods: The clinical diagnosis, based on CT scans of the brain, was made and immunohistochemic neuropathological examinations were performed in patients with intracerebral hemorrhages due to CAA. Cerebral amyloid angiopathy was diagnosed according to the Boston criteria. The Vonsattel and Mountoy scales were used to assess the grade and score of CAA. Atherosclerosis was assessed according to a four-grade scale presented in the Coding Guide from Collaborative Study of Epidemiological Factors in Cerebral Vascular Disease. Results : Of the 189 patients who died due to intracerebral hemorrhages 42 (22%) presented CAA. According to the Vonsattel scale this group comprised 32 (76%) patients who showed severe, 6 (14%) moderate and 4 (10%) mild CAA. Atherosclerosis was diagnosed in the CAA group of patients as follows: 6 (14%) with grade 1; 20 (49%) with grade 2; 9 (20%) with grade 3; and 7 (17%) patients with grade 4. Conclusions : There was no correlation between CAA and AS. The CAA was probably the direct cause of death in part of cases with advanced CAA. The different mechanisms presumably can cause CAA and AS.